1995
DOI: 10.1086/133677
|View full text |Cite
|
Sign up to set email alerts
|

Superhumps in Cataclysmic Binaries. VIII. V1159 Orionis

Abstract: We report photometry of the cataclysmic variable VI159 Orionis for -400 hours over 168 nights during 1992-4. The long-term light curves show that this is a dwarf nova of the SU UMa class, with normal outbursts recurring on a mean period of 4.0 days, and superoutbursts recurring on a period of 47.6 days. These periods wander slightly, as is typical of the class. High-speed photometry at minimum light, far from superoutbursts, reveals a weak photometric signal at 89.83 ±0.10 min, which is presumably the underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
81
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 34 publications
6
81
0
Order By: Relevance
“…V1159 Ori was discovered by Wolf & Wolf (1906), who gave it the name "Var.,Orionis 36.1906", and first investigated by Kippenhahn (1953) and Jablonski & Cieslinski (1992). Afterwards, its very short outburst cycle, superhumps, orbital periods, and high energy (X-ray, ultraviolet) emission have been studied by a number of authors (Nogami et al 1995;Robertson et al 1995;Patterson et al 1995;Thorstensen et al 1997;Szkody et al 1999). We can add little to the knowledge on V1159 Ori except for its supercycle period.…”
Section: V1159 Ori (No 01)mentioning
confidence: 99%
“…V1159 Ori was discovered by Wolf & Wolf (1906), who gave it the name "Var.,Orionis 36.1906", and first investigated by Kippenhahn (1953) and Jablonski & Cieslinski (1992). Afterwards, its very short outburst cycle, superhumps, orbital periods, and high energy (X-ray, ultraviolet) emission have been studied by a number of authors (Nogami et al 1995;Robertson et al 1995;Patterson et al 1995;Thorstensen et al 1997;Szkody et al 1999). We can add little to the knowledge on V1159 Ori except for its supercycle period.…”
Section: V1159 Ori (No 01)mentioning
confidence: 99%
“…Osaki 38) has demonstrated that the short supercycle and the short normal outburst cycle of ER UMa itself can be explained by the TTI model as a system having a higher mass transfer rate. It was a puzzle in observations of the ER UMa stars that superhumps in large amplitude were observed already during the rising branch of the superoutburst (see, observations of V1159 Ori 39) and ER UMa 40) ). In the standard scenario, the superhumps were expected to appear the later during the superoutburst the lower the mass ratio is, because of their slower growth rates.…”
Section: )33)mentioning
confidence: 99%
“…We found that the harmonics of the main frequency are slightly displaced towards higher frequencies. This effect is reported in a few superhumpers (Patterson et al 1995a andHarvey &Patterson 1995).…”
mentioning
confidence: 52%
“…A third periodicity of 0.083204 d « 2.00 hr appeared in 1994 but not in 1995. It may be related to the recently discovered anti -superhump phenomenon (Patterson et al 1993, Harvey et al 1995, Patterson 1995and Patterson et al 1995a.…”
mentioning
confidence: 96%